The Voices of Preservice EFL Teachers on the Implementation of Teacher Educators‘ - Effendi Limbong (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
ABSTRACT This research investigate pre-service EFL teachers’ voices toward teacher educators’ implementation of flipped classroom combined with Facebook throughout TPACK that can be observed by pre-service EFL teachers during their teacher training program. This study employed phenomenology of semi-structure interview and document e-portfolio projects of eight pre-service EFL teachers. This research revealed although not all participants were unfamiliar with flipped classroom, this approach to combine with Facebook as media to upload e-portfolios of previous pre-service EFL teachers and various website links to design and develop PACI model was effective and efficient in understanding the content of PACI model before they have face to face classes. The significance of this study is useful for pre-service EFL teachers to witness the use flipped classroom combine with Facebook to extend the use of technology for being self-discipline and self-directness to design and develop PACI model throughout the TPACK framework in supporting them to be 21st future teachers. ABSTRAK Penelitian ini mengungkap pengalaman para calon guru terhadap penerapan kelas terbalik dengan menggunakan Facebook sebagai media oleh dosen dengan TPACK yang dapat diamati oleh para calon guru selama mengikuti perkuliahan agar nantinya dapat mereka terapkan. Dengan menggunakan phenomenology semi interview terstruktur terhadap delapan calon guru dan menganalisa hasil unjuk kerja berbasis portofolio elektronik. Penelitian ini menemukan walaupun tidak semua calon guru terbiasa dengan pendekatan kelas terbalik, penggabungan metode ini dengan Facebook sebagai media untuk memasukkan materi ajar dari Internet ditambah dengan hasil kerja mahasiswa sebelumnya berbasis elektronik portofolio untuk mendesain dan membuat materi ajar berbasis teknologi dengan menggunakan PowerPoint, Audacity, Camtasia, dan Internet (PACI) efektif dan efisien untuk difahami dan diterapkan oleh calon guru sebelum mengikuti perkuliahan dan meningkatkan penggunaan teknologi untuk belajar mandiri, mendesain, dan membuat PACI model berdasarkan TPACK untuk menjadi guru abad 21. How to Cite: Limbong, E. (2016). The Voices of Preservice EFL Teachers on the Implementation of Teacher Educators’ Flipped Classroom in Designing and Developing PACI Model. IJEE (Indonesian Journal of English Education), 3(2), 171-191 doi:10.15408/ijee.v3i2.5511. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i2.5511